2020
DOI: 10.1101/2020.04.18.20070565
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical Characteristics of 20,662 Patients with COVID-19 in mainland China: A Systemic Review and Meta-analysis

Abstract: Coronavirus disease 2019 (COVID-19) is a global pandemic and has been widely reported; however, a comprehensive systemic review and meta-analysis has not been conducted. We systematically investigated the clinical characteristics of COVID-19 in mainland China to guide diagnosis and treatment. We searched the PubMed, Embase, Scopus, Web of Science, Cochrane Library, bioRxiv, medRxiv, and SSRN databases for studies related to COVID-19 published or preprinted in English or Chinese from January 1 to March 15, 2020… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 97 publications
0
11
0
Order By: Relevance
“…When compared with adults, most pediatric patients presented with mild or moderate clinical syndromes, and only a few were admitted to the ICU, which was much less than that of adults. As reported by Tang et al (22), almost 26-32% of adult patients were committed to the ICU. Fever and cough were the dominant symptoms in pediatric patients, of which the frequencies were lower compared with adults (55.49-78.49%).…”
Section: Discussionmentioning
confidence: 76%
“…When compared with adults, most pediatric patients presented with mild or moderate clinical syndromes, and only a few were admitted to the ICU, which was much less than that of adults. As reported by Tang et al (22), almost 26-32% of adult patients were committed to the ICU. Fever and cough were the dominant symptoms in pediatric patients, of which the frequencies were lower compared with adults (55.49-78.49%).…”
Section: Discussionmentioning
confidence: 76%
“…Furthermore, the major population comprised in this study was non-Hispanic black men whose median age was over 65 years [10]. Numerous reports have indicated that the average age of COVID-19 patients was about 50 years, and the gender distribution was nearly equal [33][34][35].…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, the major population comprised in this study was non-Hispanic black men whose median age was over 65 years [10]. Numerous reports have indicated that the average age of COVID-19 patients was about 50 years, and the gender distribution was nearly equal [3335]. However, the mortality risk for COVID-19 varies by age, older people might be related to multiple comorbidities and at a higher risk of COVID-19 -related hospitalization than young people [3638].…”
Section: Discussionmentioning
confidence: 99%
“…Elderly (70 years) patients are prone to develop the most complicated infections as confirmed in a recent meta-analysis collecting the results of 147 studies on 20,662 Chinese patients in which the mean patient age was 49 years and 53% of patients were male [ 31 ]. A significant prevalence of cardiovascular comorbidities was also described in this large Chinese cohort, including systemic hypertension (21%), diabetes mellitus (12%), cardiovascular (9%) and cerebrovascular diseases (6%) [ 31 ]. In another large report of 1099 patients with confirmed COVID-19, systemic arterial hypertension and diabetes mellitus were recorded in 23.7% and 16.2% respectively [ 32 ].…”
Section: Clinical Aspects: Increased Rate Of Thromboembolic Events Inmentioning
confidence: 99%